Defining the ideal automation level for a workstation on production lines: Case study using the PROMÉTHÉE II method - Frederico de Pinho, Gladstone; Garcia Borges de Souza, Dalton (Latin American Journal of Energy Research, 2025)
The objective of this article is to map the current level of automation of a workstation considered a bottleneck in a production line at a company that supplies products and services to the Oil and Gas sector and to identify the most appropriate level to implement. Using a case study methodology, production data was collected and production processes and their deficiencies were understood through interviews, questionnaires, documentary research, and direct observation. The DYNAMO method was used to measure the current level of automation, and the PROMÉTHÉE II multicriteria decision-making method was used to rank possible automation levels and select the most appropriate level, considering the company's technical and strategic criteria. The results allowed us to evaluate the effectiveness of the method, providing not only a possible ideal level of automation but also two possible satisfactory levels. This research contributes methodologically to the planning and optimization of production lines in industrial sectors that require greater robustness and adaptability.
Keywords: multicriteria methods; levels of automation; manufacturing